BAGAIMANA MENGEMBANGKAN PARA MANAJER MELALUI METODE INFORMAL - Muhammad Gandhi (Media Riset Bisnis & Manajemen, 2001)
It seems that the informal training may have a better result than does on training program.  Formal training is a well plan program.  The paper argues that informal program is ideally a compliment informal of a formal training.  Besides formal training, there should be an informal program which will acquaint them with a more specific jab or assignment and which undertakes their quality of expertise of individuals.